Development of dated water production function for onion at different critical stages - Alam, Md. Jawaid; Singh, AKP (Journal of Agricultural Engineering, 2000)
Experiments were carried out to study the response of irrigation on the yield of onion for the development of production function. Stress day (SD) for entire crop period was considered to quantify crop water stress and was related to yield ratio (YR). Using regression analysis the suitability of different models were tested for yield ratio (YR). The YR was related to SD to establish production function. It was found that the logarithmic model gave the best correlation and thus the logarithmic model can be used for the prediction of production function with known values of stress day.